2010
DOI: 10.1051/kmae/20010001
|View full text |Cite
|
Sign up to set email alerts
|

Fishery biology of the goldfishCarassius auratus(Linnaeus, 1758) in Lake Trasimeno (Umbria, Italy)

Abstract: Key-words: gill-net selectivity, invasive species, electrofishing, CPUEsThe fishery biology of the goldfish Carassius auratus was studied in Lake Trasimeno by analysing the selectivity of the equipment that can be used to control this invasive species. Sampling was conducted monthly from February 2003 to January 2004 by means of electrofishing, fyke-nets and gill-nets of different-sized mesh (22, 25, 28, 35, 40, 50, 70 and 80 mm

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…The optimum lengths for 70, 80, 100, 140 mm mesh size nets (mesh size bar length converted to mesh size stretched) reported as 18.97, 21.68, 27.10, 37.94 cm according to Mahon et al (2000) by Lorenzoni et al (2010) are shows a great similarity with what we reported as 19.11, 21.84, 27.20 and 38.08 cm.…”
Section: Discussionsupporting
confidence: 86%
“…The optimum lengths for 70, 80, 100, 140 mm mesh size nets (mesh size bar length converted to mesh size stretched) reported as 18.97, 21.68, 27.10, 37.94 cm according to Mahon et al (2000) by Lorenzoni et al (2010) are shows a great similarity with what we reported as 19.11, 21.84, 27.20 and 38.08 cm.…”
Section: Discussionsupporting
confidence: 86%
“…In particular, the population explosion of goldfish in the lake, following its introduction in 1988, has seriously reduced the traditional fishing activities, already impacted by the progressive decrease in water levels. Furthermore, it has contributed to the threat to southern pike and the whole ecosystem with its benthic feeding activities, which have contributed to a reduction in hydrophyte coverage, increased water turbidity and re‐suspension of nutrients that result in phytoplankton blooms (Carosi et al., ; Lorenzoni, Dolciami et al, ; Lorenzoni, Ghetti et al., ). Furthermore, goldfish can cause a negative impact on tench populations due to interspecific competition for food and habitat (Lusk, Lusková & Hanel, ).…”
Section: Discussionmentioning
confidence: 99%
“…Among these, the rapid expansion of the goldfish Carassius auratus (L.), accidentally introduced in 1988 during stocking activities with juvenile common carp Cyprinus carpio L. (Carosi, Ghetti & Lorenzoni, ), is particularly worrying due to the high invasiveness of the species (Crivelli, ). According to Lorenzoni, Dolciami, Ghetti, Pedicillo and Carosi () and Lorenzoni, Ghetti, Pedicillo and Carosi (), the use of the scientific name C. auratus in the present paper was based on diagnostic characters of the species, i.e. the number of gill rakers, the shape of the dorsal fin and the peritoneum colour (Balon, ; Kottelat & Freyhof, ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, phenotypic plasticity is regarded to be more beneficial in variable environments than in constant environments, where a single optimal phenotype may be favoured instead of maintaining plasticity in traits (Schlichting & Pigliucci, ). The thermal conditions associated with lower latitudes could be responsible for the distinct patterns in the morphology of the Italian population, as the water temperature in Lake Trasimeno often exceeds 30° C in summer (Lorenzoni et al, ) and thus differs considerably from the other sites where A. melas for this study were sampled.…”
Section: Discussionmentioning
confidence: 99%